Gametogénesis y desove de chione subrugosa (Wood, 1928) (Bivalvia veneridae) en el golfo de Nicoya, Costa Rica. (ING) - Cruz, Rafael A. (Uniciencia, 1986)
The reproductive cycle of a population of the clam Chione subrugosa was studied by means of histological methods and index of condition. The percentage of females and males was 41,7: 58,3, respectively. There was no evidence of hermaphroditism; the period of greatest spawning activity was in June, October and February. The index of condition reflected appropriately gonadic development in Ch. Subrugosa. A low increment in the temperature and a strong decrease in the salinity coincided with the spaw ning peaks.